The treatment of type 1 diabetes in children and youth - Kaufman, Francine (Henry Stewart Talks, 2013)
The SEARCH study, The latency period in the development of T1D, Time to diabetes by number of Abs, TrialNet and Immune Tolerance Network international consortia, Prevention and early diagnosis, The diagnosis of T1D in children and youth, Work up of diabetes type in youth, Catastrophe at diagnosis: DKA, What is the course of type 1 diabetes, DCCT, EDIC and rate of severe hypoglycemia, The importance of glycemic control, The insulin pump: more like a healthy pancreas, CSII reduces incidents of severe hypoglycemia, Continuous glucose monitoring, Early control and beta-cell preservation, STAR 3 study, A1C reduction is correlated with sensor use, Prevalence of CVD risk factors in youth, The role of healthcare provider in treatment, Evolution of a fully-automated delivery system, How does LGS work?, The closed-loop system